Exploring Perceptions of Pharmaceutical Vocational High School (VHS) Students toward the Importance of English for Their Future Career - Rosida, Futia; Sujannah, Wahyu Diny (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
Vocational High Schools (VHS) prepare their students to be ready to work in their fields after graduation. In this globalization era, understanding English will be beneficial and a plus point for the students when looking for a job. Thus, this descriptive qualitative research aimed to explore the perceptions of pharmaceutical VHS students regarding the significance of English for their future careers. The participants, consisting of eight twelfth-grade students who had high English scores and majored in Industrial Pharmacy, were interviewed and the findings revealed that they believed that English proficiency was crucial for their future careers as it helps in accessing international job opportunities and resources, benefiting from professional development and in-house training, and overcoming language barriers in a globalized world. Thus, it is suggested that the English curriculum should be tailored to meet the specific language needs of the pharmaceutical field and future research could explore the expectations of pharmaceutical industry employers regarding the English skills of job applicants.